Use and Outcomes of Nasotracheal Intubation Among Patients Requiring Mechanical Ventilation Across U.S. PICUs*. Issue 7 (July 2020) - Christian, Claire E.; Thompson, Nathan E.; Wakeham, Martin K.
Abstract : Objectives: The use and outcomes of nasotracheal intubation in pediatric patients requiring mechanical ventilation have not been quantified. Our goal is to identify prevalence of use, associated factors, and outcomes of nasotracheal versus orotracheal intubation in patients requiring mechanical ventilation. Design: Retrospective cohort study using deidentified data from the Virtual Pediatric Systems database. Data from PICU admissions from January 1, 2015, to December 31, 2016 were analyzed. Setting: One hundred twenty-one PICUs located within the United States. Patients: PICU admissions requiring an endotracheal tube—either nasotracheal or orotracheal—were included. Those with a tracheostomy tube present at admission were excluded from the study. Interventions: Not applicable. Measurements and Main Results: Among the 121 PICUs included in the study, 64 PICUs (53%) had zero nasotracheal intubations during the reviewed time period. There were 12, 088 endotracheal intubations analyzed, and 680 of them (5.6%) were nasotracheal. Of those patients nasotracheally intubated, most were under 2 years old (88.1%), and 82.2% of them were classified as a cardiac patient. Among these young cardiac patients, the rate of unplanned extubation was 0% in the nasotracheal intubated versus 2.1% in the orotracheal intubated group ( p < 0.001) Conclusions: Nasotracheal intubation is used in a minority of U.S. PICUs and mainly among young cardiac patients. Nasotracheal intubation is associated with a lower rate of unplanned extubations in this patient population. Future prospective studies analyzing the benefits and complications of nasotracheal versus orotracheal intubation in pediatric patients requiring mechanical ventilation are indicated.